A Facile Chemical Solution‐Based Method for Epitaxial Growth of Thick Ferrite Films. (24th August 2015) - Hong, Xiaoliang; Yang, Yang; Xiao, Wen; Yang, Yong; Chen, Jingsheng; Ding, Jun
<x xml:space="preserve">Abstract</x> Thick ferrite films are promising for various applications, including miniaturized energy harvesters, inductor‐on‐chip applications, microelectromechanical systems (MEMS), and microwave devices. Here, a wet‐chemical (thermal decomposition method) for high‐quality and epitaxial thick ferrite is successfully developed. A silicon‐technology compatible process is developed, by which highly textured Fe3O4 can be grown on a Si substrate with a MgO seed layer and patterned structures can be relatively easily realized. As‐prepared Fe3O4 thick films demonstrate their potential applications for microwave and MEMS supercapacitors. Different ferrite compounds are successfully fabricated, including Co‐ferrite with high coercivity and perpendicular anisotropy, and Ni‐ferrite with high resistivity and enhanced magnetization. The method is demonstrated to also be suitable for the deposition of thick ZnO films. High conductivity is obtained in Al‐doped ZnO thick films.